Regulatory Capital Charges for Too-Connected-to-Fail Institutions : A Practical Proposal - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2010)
The recent financial crisis has highlighted once more that interconnectedness in the financial system is a major source of systemic risk. I suggest a practical way to levy regulatory capital charges based on the degree of interconnectedness among financial institutions. Namely, the charges are based on the institution's incremental contribution to systemic risk. The imposition of such capital charges could go a long way towards internalizing the negative externalities associated with too-connected-to-fail institutions and providing managerial incentives to strengthen an institution's solvency position, and avoid too much homogeneity and excessive reliance on the same counterparties in the financial industry.